Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To answer this question, we need to remember the equation for a circle with a center at point (h, k) is given by:
[tex](x-h)^2+(y-k)^2=r^2[/tex]We have that the center of this circle is located at point (0, 4). Then, we have:
• h = 0
,• k = 4
And we also know that the point (-2, -1) lies on this circle. Then, we have:
• x = -2
,• y = -1
Therefore, we can substitute these values into the previous equation to find the radius of this circle as follows:
[tex](-2-0)^2+(-1-4)^2_{}=r^2\Rightarrow r^2=(-2)^2+(-5)^2\Rightarrow r^2=4+25[/tex]Now, we finally have that the length of the radius of this circle is (squared root of 29 units) (third option):
[tex]r^2=29\Rightarrow\sqrt[]{r^2}=\sqrt[]{29}\Rightarrow r=\sqrt[]{29}[/tex]We can represent graphically the equation of the circle as follows:
[tex](x-0)^2+(y-4)^2=(\sqrt[]{29})^2=(x-0)^2+(y-4)^2=29[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.